2019
DOI: 10.36018/dsiij.v13i.109
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Role of Two Yoga Based Mantra Recitation on Selective Attention in Undergraduate Students

Abstract: Aim of the present study was to evaluate the effect of Gayatri mantra recitation and Om recitation on selective attention as measured by color stroop. The study was performed on undergraduate students (Male=30) with age range of 18 to 30 years. All students were trained for reciting Gayatri mantra for 3 days. The baseline data were used. The participants participated in Gayatri mantra and Om recitation about 15 min for two consecutive days. The sequence of the session was assigned randomly to the participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Both the intervention led to the significant improvement in the post attention score (p=0.001). Further analysis showed that the influence of Gayatri mantra in attention was (16.16 %) slightly higher than that of Om mantra (9.26 %) (Kumar, 2019).…”
Section: Attentionmentioning
confidence: 84%
See 1 more Smart Citation
“…Both the intervention led to the significant improvement in the post attention score (p=0.001). Further analysis showed that the influence of Gayatri mantra in attention was (16.16 %) slightly higher than that of Om mantra (9.26 %) (Kumar, 2019).…”
Section: Attentionmentioning
confidence: 84%
“…But owing to its religious connotations, conceptual or theoretical explanations, its scientific scrutiny and validation has not been popularized. Only few experimental studies have reported the beneficial effects of Gayatri mantra chanting in reducing stress Sharma, 2016), anxiety (Candrawati et al, 2018;Sudha, 2020), and in improvement of cognitive function (Kumar, 2019;Pradhan & Derle 2012;Malhotra et al, 2016;Samajhdar et al, 2020;Narayan & Venugopalan, 2018) as well as the quality of life of the individuals (Dewi et al, 2020). But to conclude about its effect on mental health, wellbeing, cognitive functions and physiological parameters of health there is no any review of empirical studies present on Gayatri mantra.…”
Section: Need Of the Studymentioning
confidence: 99%